Adsorption of Ammonia Nitrogen Using Variance Melons Rind as Adsorbent - Zakeria, Nurul Rozaireen; Abdullah, Nur Farisha Azmira; Harry, Deborah Ahira; Norhayati Ngadiman, (Multidisciplinary Applied Research and Innovation, 2023)
Water treatment has been widely done by various parties involved in the removal of contaminants, organic matter, and groundwater remediation from wastewater. However, the process offers high costs and requires high maintenance. In recent years, the demand for safe and cost-effective technologies for removing contaminants from wastewater has prompted increased research interest in the development of low-cost alternatives. As a result, there is an urgent need to investigate all potential sources of agro-based affordable adsorbents and thoroughly investigate their suitability for contaminant removal. In this study, the capability of different types of melon’s rind was determined by the percentage of ammonia nitrogen reduction in synthetic wastewater. Other than that, the objective of this study is a comparison between the percentage reduction of raw and modified of both WR and HR on ammonia nitrogen adsorption. The data obtained from batch equilibrium analysis were analyzed using the Kinematic Model; adsorption capacity and removal efficiency. The ability of raw WR on adsorbing ammonia nitrogen was slightly higher than other adsorbents. The effect of modifying the melon rind of WR and HR for the adsorption of ammonia nitrogen was verified to contribute to reducing the contaminant from synthetic wastewater.